Evaluation of the endoscope disinfection effectiveness of two different disinfectants composed of benzalkonium chloride and 0.2% Peracetic acid [Benzalkonyum klorid ve %0,2 perasetik asit içerikli dezenfektanlarin endoskop dezenfeksiyonundaki etkinliğinin değerlendirilmesi] - (:unkn) unknown (Gulhane Medical School, University of Health Sciences, 2015)
Aim: The aim of this study was to evaluate disinfection efficiencies of disinfectants that are made up of quaternary ammonium compounds (QAC) and 0.2% peracetic acid (PAA) in endoscope disinfection. Materials and Methods: A single-center, prospective cohort work was continued for 12 weeks. Fifty-three endoscopes disinfected with QAC and 51 endoscopes disinfected with 0.2% PAA were included in this study. Samples were collected from endoscopes at both before and after disinfection process. For evaluation of the data, descriptive statistical methods of ratio, mean, standard deviation and for comparison of disinfectants the chi-square test were used. p value lower than 0.05 was accepted as statistically significant. Results: Any procreation of bacteria was detected on the surface and in the both aspiration and air-water channels of the endoscopes disinfected with 0.2% PAA, while some procreation were observed surface and both channels of the endoscopes disinfected with QAC. Statistically significant difference was found between disinfectants in the disinfection efficiencies for both channels (p < 0.05), although no difference was found those for surface of endoscopes (p > 0.05). Conclusion: It can be concluded that the disinfection efficiency of 0.2% PAA is significantly higher than QAC in endoscope disinfection. © Gülhane Askeri Tip Akademisi 2015.
Keywords: %0.2 peracetic acid; Benzalkonium chloride; Disinfection; Endoscopy